The training needs of primary school leaders in Al-Kharj governorate in light of the transformational leadership requirements - Al-Hababi, Saleh Hadi Sharie (Journal of Educational and Psychological Sciences, 2021)
The study aimed to determine the training needs of primary school leaders in Al-Kharj governorate in light of the transformational leadership requirements from their point of view regarding the dimensions of (leadership attractiveness - inspirational communication - mental stimulation - personal appreciation). The researcher used the descriptive survey approach. It was applied on a sample of (44) Leader in primary schools in Al-Kharj governorate and the tool was a questionnaire. The results of the study revealed; The tool obtained an overall mean (3.38 out of 4) at the dimensional level; The leadership attractiveness dimension got the highest average (3.50 out of 4), then after inspirational communication with an average (3.40 out of 4), then after personal appreciation with an average (3.37 out of 4), and finally after mental stimulation with an average (3.26 out of 4), all of them rated as need (big); based on the results of the study, the researcher presented a set of recommendations and proposals.
Keywords: Training needs; primary school leaders; Al-Kharj governorate; transformational leadership requirements